Comparação interpopulacional de caracteres morfológicos e reprodutivos do ouriço-do-mar Arbacia lixula (Linnaeus, 1758) (Echinodermata: Echinoidea) em duas localidades do litoral do estado do Rio de Janeiro - Zama, Paula Caetano (2005)
Arbacia lixula (Linnaeus, 1758) is a common echinoid on the Brazilian coast, although there are few studies about this species in the South Atlantic Ocean. This work aims to compare morphological and reproductive traits in two sea urchin populations and verify the reproductive cycle of Arbacia lixula using gonadal index, maturity index and histological analysis of the gonads. Monthly 15 to 20 specimens were collected by free diving in Prainha, Arraial do Cabo and in Ponta de Itaipu, Niterói. The specimens captured were weighed and had the test diameter and height measured before dissection. The body components indexes were calculated. Each specimen had one gonad analyzed histologically to verify gametogenic stages. The reproductive cycle was fast and continuous showing production and spawning of gametes all the period. Morphological differences were found among diameter, height, and weight of the tests and length of Aristotle's lantern. The results of this study suggest that phenotypic plasticity and gene flow between these two populations of Arbacia lixula should be occurring. Studies on population genetics and ecology should be done before any commercial explotation of this species.